Semi refined carrageenan-nanocomposite film incorporated with Bentong ginger extracts for active food packaging: Synthesis and characterization - Subramaniam, Sarmilaah Dewi; Anak Ungka, Mithrel Loxzyana; Tong, Jing Hao; Nur Annis Sofea, Rahimi; Lia Maisarah, Zakaria; Nurul Aini, Mohd Azman (Elsevier Ltd, 2024)
Bentong Ginger (BG), Malaysia patented ginger consist of various bioactive compounds such as gingerols which account for the various pharmacological benefits in human including antioxidant, antimicrobial, and anticancer. The objective of this work was to analyze the effectiveness of BG extracts as an antioxidant additive in plasticized semi refined carrageenan-nanocellulose (CN) to produce active packaging films at concentrations ranging from 5 to 20 % (v/v). The bioactive constituents in BG extracts were discovered using Liquid Chromatography Quadrupole Time-Of-Flight Mass Spectrometry (LC-QTOF/MS) and the possible interaction between the semi refined carrageenan-nanocellulose film network and BG were revealed using Fourier-Transform Infrared (FTIR) Spectroscopy. The effects of BG extracts formulated in CN film on the antioxidant release, physical and mechanical properties of the films were studied. The CN film with 20% BG improved the most, exhibiting excellent mechanical and physical properties as well as antioxidant release tests that revealed the highest release of antioxidant and total phenolic content in 95 % food simulants up to 28 days storages. This study validated that incorporation of BG extract can a promising natural additive for active packaging materials.